PELUANG PENERAPAN PRODUKSI BERSIH PADA USAHA KECIL BATIK CAP (STUDI KASUS PADA TIGA USAHA INDUSTRI KECIL BATIK CAP DI PEKALONGAN) - Sugiyarti, Gita; Mardiyono, Aris (STIE Pelita Nusantara, 2023)
This community service activity is in partnership with small and medium batik businesses. The partner location is in the city of Pekalongan. Our target is batik owners/managers in the city of Pekalongan. One of the visions is to train batik owners to be skilled, independent and able to get opportunities to implement clean production. So training is needed regarding knowledge of various opportunities for implementing cleaner production. The solution method is to provide training on implementing cleaner production. The results of this activity can increase the knowledge and skills of batik owners thereby increasing their competence.